2005
DOI: 10.1093/eurheartj/ehi111
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum neopterin predicts future adverse cardiac events in patients with chronic stable angina pectoris

Abstract: Serum neopterin is an independent predictor of major adverse coronary events in patients with chronic stable angina pectoris. This marker of macrophage activation may be useful for risk stratification in patients with chronic stable angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 33 publications
5
86
3
3
Order By: Relevance
“…Previous clinical studies have demonstrated that neopterin is associated with atherosclerotic plaque instability in coronary artery disease (CAD) [6][7][8][9][10][11][12][13][14][15][16][17] . Circulating levels of neopterin have been reported to be higher in patients with acute coronary syndrome (ACS) than in control subjects and in patients with stable angina pectoris (SAP) 6,7) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have demonstrated that neopterin is associated with atherosclerotic plaque instability in coronary artery disease (CAD) [6][7][8][9][10][11][12][13][14][15][16][17] . Circulating levels of neopterin have been reported to be higher in patients with acute coronary syndrome (ACS) than in control subjects and in patients with stable angina pectoris (SAP) 6,7) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 99%
“…These findings suggest that neopterin is an important biomarker of plaque instability in both coronary and carotid atherosclerotic lesions. [6][7][8][9][10][11][12][13][14][15][16][17][18] . In this review, we focus on the relationship between neopterin and plaque instability in coronary and carotid arteries, and also introduce the results of our recent studies.…”
mentioning
confidence: 99%
“…Likewise, in patients with cardiovascular, neurodegenerative and autoimmune disorders, rather close associations have been described between the concentrations of total homocysteine and immune activation and inflammation markers: for example, neopterin (7,8) and C-reactive protein (9), which themselves are significant predictors of cardiovascular risk (10)(11)(12). Neopterin concentrations serve as a reliable immune response marker because a great amount of neopterin is released by monocyte-derived macrophages and dendritic cells upon stimulation with Th1-type cytokine interferon-γ (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…(34), akut miyokart enfarktüslü (MI) hastaları sağlıklı kontrol grubu ve KAP'lı hastalarla karşılaştırdığında neopterin düzeylerini akut MI'lı hastalarda yüksek bulmuşlardır. Kararlı anjina pektorisli 297 hastanın 1 yıllık takiplerinde neopterinin majör kardiyak olayların bağımsız prediktörü olduğu gösterilmiştir (7). Artmış neopterin düzeyleri ayrıca hipertansif ve tıkayıcı olmayan koroner arter hastalıklı bireylerde istenmeyen kardiyak olay gelişimi ile (35) ve koroner revaskülarizasyon yapılan hastalarda hastalığın hızlı seyri ile ilişkili bulunmuştur (36).…”
Section: Discussionunclassified
“…C-reaktif protein (CRP), koroner arter hastalığı risk faktörlerinden bağımsız olarak iskemik olaylar için güçlü bir belirteçtir (5,6). Benzer şekilde, inflamasyonla ilişkili bir belirteç olan neopterin de kararlı anjina pektorisli (KAP) hastalarda kardiyovasküler olayları öngördürücü bir piteridin bileşiğidir (7).…”
Section: Introductionunclassified